Endurance in Extreme Work Environments - Cham, Belinda (Curtin University, 2021)
Extreme work environments represent complex and challenging settings in which optimal performance is required rather than optional. This thesis advances knowledge of how demands and constraints within extreme work environments impact sustained human performance over time. This thesis establishes a theoretical framework of endurance that models ongoing human performance in extreme work-life systems; and provides empirical evidence on the different ways complex work demands can impact short- and long-term endurance in real-world extreme work environments.